Temporomandibular joint biomechanics and equine incisor occlusal plane maintenance - Sterkenburgh, Tomas Rudolf; Hartl, Bettina; Peham, Christian; Nowak, Michael; Kyllar, Michal; Kau, Silvio (Frontiers in Bioengineering and Biotechnology, 2023)
In equine dentistry, the physiological incisor occlusal surface is visually perceived as a plane with a distinct inclination to the head's coronal plane, extending rostro-ventrally to caudo-dorsally. To better understand the formation of this inclined plane and its connection to tooth wear, we investigated the hypothesis that it arises from masticatory movements and the considerable distance between mandibular articular heads and the incisor occlusal surfaces, acting as the three points of support for the mandible. Leveraging data from a large-scale clinical study involving static and dynamic orthodontic measurements in horses, we approximated the mandibular movement range where incisor occlusion and tooth wear occur. By introducing and testing a segment coordinate system, we explored possible angular deviations from the occlusal plane caused by mandibular roll and pitch rotations during two lateral mandibular movement patterns, protrusion, and retrusion. Theoretical biomechanical calculations and simulations confirmed the visual perception of the incisor occlusal surface as a plane. To further examine our assumptions, we employed a simple mechanical simulator to assess incisor normal occlusion and provoked malocclusions (diagonal, smile, and frown bite) by modifying temporomandibular joint movement patterns. The results from clinical investigations were corroborated by both the theoretical analysis and mechanical simulations, strengthening our understanding of the biomechanical basis behind the physiological incisor occlusal plane maintenance in horses. These findings have significant implications for equine dental health and contribute to a thorough understanding of temporomandibular joint dynamics.